Self-initiated expatriates' cross-cultural training and cross-cultural issues: case study at ABC e-commerce company, Malaysia - Selvi Ranjit, Ranjit Singh (2020)
Globalization is moving fast, and expats migrating from one country to another is familiar and expanding more quickly than before. Due to this borderless world, crosscultural issues and training needs attention. However, there is a lack of awareness in terms of cultural issues and training provided to expatriates in Malaysia. Given that ABC E-Commerce Company consistently hires expatriates to run their day to day business, cross-cultural issues, and training should be an essential topic considered. This study examines the adjustment issues faced by self-initiated expatriates during their first six months at ABC E-Commerce Company, Kuala Lumpur, and create and propose a cross-cultural training framework for Abc E-Commerce Management. In this study, ABC E-Commerce Company was selected, and twelve (12) participants from various backgrounds, resident month/year, nationalities, and age were randomly selected. Since the author of this study works at ABC E-Commerce Company, a face to face interview was conduct with all twelve participants. Semi-structured interview questions used to get an in-depth explanation from each participant. The data was gathered from the discussion and analyzed using content analysis. The finding indicated that there are eight (8) themes obtained from the interview data. The themes analyzed from the interview data are Language, Culture and Lifestyle, Food Availability and Preferences, Expatriation Cost, Society, Cultural Etiquette, Tax and Visa Regulation, and Others. These themes are common issues faced by all twelve participants. There are thirteen (13) areas of training suggested. The areas are Culture and Demographics, Food Choices and Eating Manners, Accommodation, Communication, and Language, Tax and Visa Regulation Information, Dress Code, Transportation Information, Do’s and Don’t, Buddy System, Religious Place, Tour Guide, Health Care Information, and Electrical Appliances. The result of this research will be helpful to the expatriates in the ABC E-Commerce Company and within Malaysia. Future studies should focus on other regions within Malaysia and other companies.